Bridging the Digital Divide : How E-Integration and Supply Chain Strategy Harmonize Ambidextrous Innovation - Zenita Afifah Fitriyani (JURNAL ECONOMINA, 2026)
Innovation ambidexterity has emerged as a fundamental strategic requirement for organizations striving to maintain competitive advantages in an increasingly digitized global market. This study aims to synthesize current research on service innovation ambidexterity, specifically exploring how firms balance exploratory and exploitative innovations through digital and social integration. The research employed a systematic literature review methodology, analyzing high-impact studies indexed in Scopus and Web of Science published between 2016 and 2025. Following the PRISMA framework, a thematic synthesis was conducted on 174 initial records, focusing on empirical evidence from diverse sectors including manufacturing, banking, and hospitality. The findings reveal that digital supply chain capabilities and transformational leadership are the primary catalysts for ambidextrous outcomes. Internal and external supply chain integration were found to significantly mediate the relationship between technological visibility and product innovation. Notably, while e-integration drives exploitative efficiency, its impact on exploratory innovation is subject to suppression effects by rigid supply chain strategies. Furthermore, informal social relations and relational capabilities were identified as vital drivers of supplier-led innovation in emerging economies. The study concludes that achieving innovation balance requires a synchronized approach of digital prowess and strategic flexibility. These findings imply that managers must move beyond standard integration to foster relational agency, providing a roadmap for sustaining operational performance amidst market volatility.